If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 2g Solving 18 = 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. 18 + -2g = 2g + -2g Combine like terms: 2g + -2g = 0 18 + -2g = 0 Add '-18' to each side of the equation. 18 + -18 + -2g = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -2g = 0 + -18 -2g = 0 + -18 Combine like terms: 0 + -18 = -18 -2g = -18 Divide each side by '-2'. g = 9 Simplifying g = 9
| .25v-.42=.28v-.25 | | -4(x-3)-13=3(x+2) | | V=(10-2x)(8-2x) | | c(3)=15 | | 2x^2=13x+24 | | 6+2x=-6x-90 | | 5x-10+1x+3=8 | | 13+5r=2(5+2r) | | 4(7x+4)-9=28x+7 | | x^3+5x+3x+15=0 | | 4a+2=3a+7 | | 0=-4x^2-16x+20 | | 201(6+6)= | | 2-4h=6-6h | | -50+1.0x=300 | | 4x-3=-103-6x | | Y=-4x-16x+20 | | 2x+5-8w=7-4w | | 3m+3-m=3(m+1) | | -1v+5+4v=1+5v+3 | | (2i+3)(7i+6)= | | 9x+6(3x-4)=12-9x | | 3a-11=4(a+1)+13a+3 | | 2g-8+3g=7 | | .17(x+29)=86 | | 2x-6=5x+27 | | 2y^2-7y-10=0 | | 4x-2(.50-1)=14 | | 101(87+13)= | | y^3+729= | | 4x-2(x-2)=-7+4x+5 | | 9x-12=84 |